Writing the materials and methods - Ng, Kwan Hoong; Peh, W.C.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
When writing scientific papers to share their research findings with their peers, it is not enough for researchers to just communicate the results of their study; it is equally important to explain the process by which they arrived at their results, so that the study can be replicated to validate the observations. The materials and methods section is used to describe the experimental design and provide sufficient details so that a competent colleague can repeat the experiment. A good materials and methods section will enable readers to evaluate the research performed and replicate the study, if necessary.